EFFECTS OF SOWING DATE AND LOCATIONS ON THE SELECTED WHEAT CULTIVARS QUALITY PERFORMANCE - Abdulla, Sh. S.,; K. M. Mustafa,; D. A. Sabir, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The current study was aimed assessing the effects of cultivars, sowing date and locations on bread wheat (Triticum aestivum L) quality parameters grain protein concentration (GP), Gluten Index GI, falling number (FN), Water absorption capacity (WAC %), Pasting temperature (PT), and loaf volume (LV) of five bread wheat cultivars viz. Alla, Hassad, Charmo, Maaroof, and Adana as control, two sowing dates (Nov 15th, Dec 15th) at each location under rainfed environment. Grain samples were obtained from previous field experiments were conducted at two locations of Sulaimani Governate in Iraq-Kurdistan-region, Qlyasan and Halabja, during growing seasons 2018-2019. The experiments were conducted using RCBD within split plot arrangement with three replicates. Result for companied analysis, showed that cultivars sowing date, locations, the interactions CS, CL, and SL and tri-interaction CSL were high significantly affects to all quality traits except GP for location, LV for SL and GP for CS interaction, which were non-significant. The results confirmed that sowing wheat lately is an accept option for maximizing GP, GI, PT, and LV, while, optimum sowing was increasing FN and WA traits, regardless of cultivar or location. Wheat grown at Qlyasan appeared to have more GP content, FN, WA, PT, and LV, while Halabja location to have stronger gluten quality (GI). The di-interactions viz. CS, CL, and SL and tri-interaction CSL played a significant important role in changing or modifying the values of the quality traits.